Hypocoristics in Andean Ancash family speech - Julca Guerrero, Félix (2004)
This paper presents the preliminary results of an empirical investigation of a linguistic and cultural phenomenon that operates daily in Ancash Andean speech: hypocoristics. In the Andean area of Ancash, Quechua and bilingual (Quechua-Spanish) speakers frequently use Quechua and Quechuaized hypocoristics in their daily communications with the intention of expressing affection, affection and trust to their interlocutors. However, the forms of familiar and friendly treatment by means of hypocoristics have not yet deserved a complete and sufficient study.